Inhibition of id-1 reduces osteosarcoma growth and metastasis through mediation of snail - Rongbing Shu; Zhuanyi Yu; Jianmin Wu; Qiuxin Cheng; Zhihao Peng; Huaqiang Zhou; Min Zhao (Journal of Orthopaedic Surgery and Research)
Abstract Objective Osteosarcoma (OS) is a highly invasive bone tumor that frequently metastasizes to the lungs. This study aims to investigate the role of the Id-1 gene in OS invasion and metastasis, and its relationship with the Snail gene. Methods This study included tissue samples from 12 non-metastatic osteosarcomas and 9 metastatic osteosarcoma patients to examine the expression of Id-1 and Snail using RT-qPCR and analyze their correlation. In cell-based experiments, four osteosarcoma cell lines (Saos-2, U2OS, MG-63, and 143B) and the human osteoblast cell line hFOB 1.19 were cultured. The expression of Id-1 and Snail was evaluated by RT-qPCR and Western blotting.Cells were randomly divided into the Control group, sh-NC group, and sh-Id-1 group using lentiviral infection. Transwell invasion and scratch assays were used to assess cell migration and invasion. WB was employed to detect the expression of Id-1, Snail, and epithelial-mesenchymal transition (EMT)-related proteins (E-cadherin, vimentin, and N-cadherin) in the OS cells of each group. In animal experiments, Tumor formation in each group was evaluated by injecting cells subcutaneously into mice. An osteosarcoma lung metastasis model was established by injecting infected cells into the tibia of mice. Tumor growth and lung metastasis were observed using HE staining. The expression of Id-1, Snail, and EMT-related proteins in osteosarcoma and lung tissues from each group of mice was assessed using Western blot and immunohistochemistry. Results The expression of Id-1 and Snail was significantly higher in osteosarcoma tissues than in normal bone tissues, and the expression of Id-1 was positively correlated with that of Snail. In cell experiments, downregulation of Id-1 reduced Snail expression and significantly inhibited EMT, as well as the migration and invasion of OS cells (P < 0.05). In animal experiments, compared to the Control group, the sh-Id-1 group mice was no significant change in body weight, but the tumor volume was significantly reduced, and fewer lung metastatic nodules (P < 0.05). HE staining indicated decreased nuclear atypia, reduced invasion and destruction, fewer new blood vessels, and less calcification in the sh-Id-1 group tumors. Immunohistochemistry and WB results showed upregulation of E-cadherin and downregulation of vimentin, N-cadherin, Id-1, and Snail in the sh-Id-1 group (P < 0.05). Conclusion Downregulation of Id-1 inhibits the EMT process by reducing Snail expression, effectively suppressing the growth, invasion, and lung metastasis of OS.